Using asynchronous quantitative computed tomography for opportunistic screening of osteoporosis - A. V. Petraikin; N. V. Toroptsova; O. A. Nikitsinskaya; S. Yu. Kuznetsov; L. A. Nisovtsova; E. S. Akhmad; Z. R. Artykova; D. S. Semenov; K. A. Sergunova; A. V. Vladzymyrskyy; S. P. Morozov (Научно-практическая ревматология)
The aim – to determine the possibility of identifying individuals with osteoporosis using asynchronous computed quantitative tomography (CT) of the proximal femur by comparison with dual-energy X-ray absorptiometry (DХA).Materials and methods. The study included 40 postmenopausal women and 6 men over 50 years old (Me of age – 72.5 [65.3; 77.7] years) referred by the attending physician for densitometric examination. The patients signed an informed consent. The measurements were performed on a DXA with a narrow fan beam (Lunar Prodigy Advance, GE Healthcare, USA), and QCT on the Aquilion 64 (Canon Medical Systems, Japan). Correlation analysis and comparison of projected bone mineral density (BMD), bone mineral content (BMC), measurement area and T-score using the Blend – Altman method were carried out.Results. A statistically significant correlations were revealed between the indicators of DXA and asynchronous QCT: for femoral neck BMD r=0.93; for the T-score r=0.93; for the total hip – r=0.91 and r=0.91 respectively. When conducting the analysis using the Blend – Altman method, it was found that the QCT underestimated the value of the femoral neck BMC (bias –0.923 g), covered a smaller area of interest (bias 0.376 cm2 ), and therefore there was a shift in the values of BMD by –0.224 g/cm2 . The value of the T-score for the femoral neck had bias –0.29 standard deviations (SD), and for the total hip –0.72 SD, which were statistically significant.Conclusions. There was a high correlation between quantitative indicators of bone tissue of the proximal hip, assessed using QCT and DXA. The BMD and T-score values for the femoral neck and the total hip at QCT were lower compared to the values of the DXA results. Considering the conducted research, it is recommended that when introducing asynchronous QCT into clinical practice to identify people with osteoporosis, a synchronous phantom should be pre-scanned to compare the QCT and DXA results, followed by adjusting the BMD and T-score values for QCT by the average difference between them.